The effects of hemodilution on coagulation in term parturients: an in vitro study utilizing rotational thromboelastometry. (19th May 2022) - Getrajdman, Chloe; Sison, Matthew; Lin, Hung-Mo; Katz, Daniel
Abstract: Objective: To examine the impact of hemodilution on components of blood coagulation using rotational thromboelastometry (ROTEM ® ) in term parturients Methods: This is a prospective, observational pilot study including 35 healthy, parturients at term (≥37 weeks) without history of bleeding or clotting disorder or on medication affecting coagulation. Venous blood samples were collected and divided into specimen tubes to generate varying degrees of hemodilution with Plasma-Lyte (0%, 20%, 25%, 30%, 35%, 40%, 45%, 55%, 60%, 65%, 70%, 75%, 80%). ROTEM ® was performed to assess for coagulation changes. Results: EXTEM (extrinsically activated assay) clotting time (CT) became prolonged at 65% hemodilution and above, and the median CT was in the coagulopathic range (>80 s) at a dilution of 80%. FIBTEM (extrinsically activated assay with platelet inhibitor) amplitude at 5 min (A5) began to diminish at 35% hemodilution, with the median A5 in the coagulopathic range (<12 mm) at 55% hemodilution. The area under the curve (AUC) for EXTEM and FIBTEM consistently declined as hemodilution increased. Greater decreases in FIBTEM AUC were seen compared to EXTEM AUC, with the ratio of FIBTEM:EXTEM AUC at each dilution demonstrating a statistically significant difference from baseline. Conclusion: All thromboelastometry values demonstrated a hypocoagulable trend as hemodilution increased. However, the samples analyzed by the FIBTEM assay trended toward a coagulopathy at a lower degree of hemodilution compared to the EXTEM assay. As FIBTEM tests analyze the role of fibrinogen in hemostasis and EXTEM tests analyze the role of platelets, our findings suggest that platelets may be able to withstand higher degrees of hemodilution before impairing hemostasis compared to fibrinogen. These findings support the growing body of literature that in early stages of severe obstetric hemorrhage, the prioritization of fibrinogen replacement may be critical in preventing further coagulopathy.